HUBUNGAN PERHATIAN ORANG TUA TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS V SD SWASTA MASEHI 3 KABANJAHE - Anes Marsela Br Pelawi; Jainal Togatorop; Ferdinand Sinuhaji (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the relationship between parental attention and the learning outcomes of fifth-grade students at SD Swasta Masehi 3 Kabanjahe in the Academic Year 2025/2026. This research employed a quantitative approach using an ex post facto method with a correlational research design. The population of this study consisted of all fifth-grade students at SD Swasta Masehi 3 Kabanjahe, totaling 30 students, who were also used as the research sample. Data collection techniques included questionnaires to measure parental attention and documentation to obtain students’ learning outcomes. The research instruments were tested for validity and reliability, while data analysis involved normality testing, hypothesis testing using the t-test (partial), and simple linear regression analysis with the assistance of SPSS software. The results of the study indicate that parental attention has a significant relationship with students’ learning outcomes, as shown by: (1) the learning outcomes of fifth-grade students at SD Swasta Masehi 3 Kabanjahe in the Academic Year 2025/2026 being in the good category, with an average score of 82.7; (2) parental attention toward fifth-grade students being in the very good category, as indicated by an average parental attention percentage of 85.64; and (3) a significant relationship between parental attention and students’ learning outcomes. This is evidenced by the results of hypothesis testing, which show a calculated t value of 5.441 greater than the t table value of 2.052, with a significance value of Sig. = 0.000 < 0.05. Therefore, the higher the level of parental attention, the better the students’ learning outcomes.